0048 The Association Between REM Sleep and Risk of Mortality in Three Independent Cohorts. (27th May 2020) - Leary, E B; Watson, K T; Ancoli-Israel, S; Redline, S; Yaffe, K; Ravelo, L A; Peppard, P E; Zou, J; Goodman, S; Mignot, E; Stone, K L
Abstract: Introduction: Sleep disorders and sleep characteristics have been linked to higher risk of mortality. Despite the emerging evidence of a sleep-mortality association, the relationship between sleep architecture and mortality aren't well understood. We hypothesize that reduced REM is associated with increased mortality risk. Methods: The Osteoporotic Fractures in Men (MrOS) study is a population-based study of 2, 675 older men. Cox regression was used to evaluate the association between %REM and mortality rate. Potential covariates were evaluated using 6-fold cross validation. Sensitivity analyses were performed to rule out alternative explanations. Wisconsin Sleep Cohort (WSC) and Sleep Heart Health Study (SHHS) data were used to replicate the findings. Results: The MrOS sample mean age was 76.3 years (SD=5.51) and the median follow-up time was 12.1 years. There was a 13% higher rate of mortality for every absolute 5% reduction in REM sleep (HR=1.13, 95%CI, 1.08–1.19) after adjusting for multiple demographic, sleep, and health covariates. The association persisted for cardiovascular disease-related mortality (CVD) (HR=1.18, 95%CI, 1.09–1.28), cancer-related mortality (HR=1.14, 95%CI, 1.03–1.26), and other mortality (HR=1.19, 95%CI, 1.10–1.28). The WSC included 45.7% women. The mean age of the 1, 388 individuals analyzed was 51.5 (SD=8.5); the median follow-up time was 20.8 years. The effect size for 5% reduction in REM on rate of all-cause mortality was similar in this cohort despite the younger age, inclusion of women, and longer follow-up period (HR=1.17, 95%CI, 1.03–1.34). SHHS data is still being analyzed; however the unadjusted model is consistent with the other cohorts. Conclusion: We found an association between reduced REM and mortality in two, possibly three independent cohorts, which persisted across different causes of death and multiple sensitivity analyses. Mechanistic studies are needed and strategies to preserve REM may influence clinical therapies and reduce mortality risk. Support: NHLBI provides funding for the MrOS Sleep ancillary study "Outcomes of Sleep Disorders in Older Men" under grant numbers: R01 HL071194, R01 HL070848, R01 HL070847, R01 HL070842, R01 HL070841, R01 HL070837, R01 HL070838, and R01 HL070839. Wisconsin Sleep Cohort was supported by R01HL62252, RR03186, and R01AG14124 from the NIH. Dr. Redline was partially supported by NHLBI R35 HL135818.